The effect of empowering leader behavior on innovative behavior and job engagement: The moderating effect of supervisor trust and learning organization - Jung, SunHwa; Tak, JinKook (Korean Journal of Industrial and Organizational Psychology, 2013)
The purpose of this study was to examine not only the relationships between empowering leader behavior and innovative behavior and job engagement, but also the moderating effects of supervisor trust and learning organization on the relationships between empowering leader behavior and outcome variables. Data were obtained from 207 employees who are working in various organizations. The results of correlation analysis showed that empowering leader behavior was positively related to innovative behavior and job engagement. Supervisor trust and learning organization moderated the relationships between empowering leader behavior and innovative behavior and job engagement. Finally, the implications and limitations of this study and the directions for future research were discussed.